2017
DOI: 10.1021/acsnano.7b02999
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of Graphene Oxide Membranes in Aqueous Solution: Characterization of Interlayer Spacing and Insight into Water Transport Mechanisms

Abstract: Graphene oxide (GO) has recently emerged as a promising 2D nanomaterial to make high-performance membranes for important applications. However, the aqueous-phase separation capability of a layer-stacked GO membrane can be significantly limited by its natural tendency to swell, that is, absorb water into the GO channel and form an enlarged interlayer spacing (d-spacing). In this study, the d-spacing of a GO membrane in an aqueous environment was experimentally characterized using an integrated quartz crystal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
440
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 617 publications
(457 citation statements)
references
References 62 publications
(83 reference statements)
14
440
2
1
Order By: Relevance
“…These studies focused on the mechanical properties of the GO materials and showed that the integration improved the connectivity of the GO nanosheets, which led to an increase in both tensile strength and toughness.C ovalent crosslinking by esterification using dicarboxylic acids could control the physical properties of the nanosheet membranes ( Figure 2a). [14] Covalent crosslinking through crosslinkers containing hydroxyl groups resulted in ar egular interspacing of 0.76 nm, with less swelling tendency,d epending on the type of crosslinker.T he crosslinking of GO nanosheets also increased the elastic moduli from 0.03 to 3.49 GPa. Thei nterlayer spacing of pristine GO is about 0.69 nm but is increased to 6-7nminthe aqueous state due to its high swelling tendency.…”
Section: Graphene-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies focused on the mechanical properties of the GO materials and showed that the integration improved the connectivity of the GO nanosheets, which led to an increase in both tensile strength and toughness.C ovalent crosslinking by esterification using dicarboxylic acids could control the physical properties of the nanosheet membranes ( Figure 2a). [14] Covalent crosslinking through crosslinkers containing hydroxyl groups resulted in ar egular interspacing of 0.76 nm, with less swelling tendency,d epending on the type of crosslinker.T he crosslinking of GO nanosheets also increased the elastic moduli from 0.03 to 3.49 GPa. Thei nterlayer spacing of pristine GO is about 0.69 nm but is increased to 6-7nminthe aqueous state due to its high swelling tendency.…”
Section: Graphene-based Materialsmentioning
confidence: 99%
“…[1] Nanosheet membranes were first used in ion separation applications for water or liquid treatment processes such as nanofiltration and ultrafiltration. [14] Preventing their swelling during the separation process and maintaining high membrane performance are the key issues for graphene-based membranes. [14] Preventing their swelling during the separation process and maintaining high membrane performance are the key issues for graphene-based membranes.…”
Section: Ion Separationmentioning
confidence: 99%
“…

Lignin-based cations introduced into graphene oxide (GO) have been found to bring about stabilization of the nanostructure and the active sites and to give rise to various interactions for subsequent modification with polyelectrolyte and nanospacers,w ith av iew to precisely controlling the nanochannels of the GO-based membranes.T he resulting membranes exhibited excellent performance in biofuel dehydration with water flux of 4000-6000 gm À2 h À1 ,w hich exceeds that of the stateof-the-art polymericand GO-based membranes.

Graphene-based membranes have emergedo ver the past few years as promising materials for diverse separation applications, such as water purification, solvent dehydration, and gas separation. [4] However, GO membranes can swell or even crack when immersed in aqueous solutions, [5] whereupon the stacked nanochannels are disrupted and the practical performance is significantly compromised. [2] Grapheneo xide (GO) has been the most frequently employed derivativeo fg raphene for developing such membranes, owing to its abundant oxygenated groups, [3] which enable its dispersion in water and greatly improvet he possibilities for assembly of membrane nanostructures, including laminates and hybrids.

…”
mentioning
confidence: 99%
“…[1] Atomically thin graphene nanosheets endow membranes with at hinner active layer and sub-nanometersized pores, affording greater permeation flux and more-selective moleculart ransport, respectively. [4] However, GO membranes can swell or even crack when immersed in aqueous solutions, [5] whereupon the stacked nanochannels are disrupted and the practical performance is significantly compromised. [4] However, GO membranes can swell or even crack when immersed in aqueous solutions, [5] whereupon the stacked nanochannels are disrupted and the practical performance is significantly compromised.…”
mentioning
confidence: 99%
“…Benefiting from the extraordinary physicochemical properties of GO nanosheets, the GO membrane has advantages in terms of its tunable separation performance, potentially ultrafast water transport, and high chemical activities to be functionalized . Unlike the tortuous cylindrical pores in the traditional polymeric membranes, separation by the GO membranes primarily relies on the ideally horizontal 2D nanocapillaries formed by the tightly stacked GO nanosheets . The protruding oxygen‐containing functional groups keep apart the adjacent GO nanosheets to form nanocapillaries suitable for separation at the NF level .…”
Section: Introductionmentioning
confidence: 99%